Faktor Penyebab Peserta Didik Stres dalam Belajar di Kelas VIII SMP N 4 Sutera Kabupaten Pesisir Selatan - Wibowo, Ari; Kasih, Fitria; Yandri, Hengki (Bimbingan dan Konseling, 2014)
The Factors of causing stress in students learning comes from within themselves and the social environment. Causes of stress in themselves, such as: the pressure exerted inside. While the external self-learners or social environment, such as: family, teachers and friends. The purpose of this study describe: 1) internal factors cause stress in students learning. 2) external factors cause stress in students learning. This research is descriptive. This study population is all students of class VIII High School First State 4 Sutera, amounting to 252 people and for sampling using proportional random sampling, taken 20% of each class by the number 49. Sources of data are primary data and secondary data. The instrument used was a questionnaire, while the formula used for the data analysis Criterium Sturgess and Percentage. The results of the study found the factors causing stress students studying in class VIII in High School First State 4 Sutera in general are pretty much in the category. The results of this study of 1) internal factors are pretty much in the category. 2) external factors are pretty much in the category.